ANALISA PENGARUH PUTARAN DAN JARAK (PITCH) PISAU TERHADAP KAPASITAS PRODUKSI LIMBAH SAWI PADA MESIN PERAJANG SAWI - Sulistyono, Djoko; Triyono, Achmad (MEKANIKA: Jurnal Teknik Mesin, 2015)
Mustard is a group of plants of the genus Brassica leaves or flowers are used as food (vegetables), both fresh and processed. Mustard Brassica species include some that are sometimes similar to each other. Onecommodity farmers in village Parengan, Krian, Sidoarjo every day requires a mixture of vegetable waste mustard asanimal feed ingredients. Livestock alone is the main food forage. Green feed cattle, namely waste mustard. Forageplays a very important because it contains all the substances necessary livestock. One of them is from the green feedlivestock waste that much mustard in the traditional market. In East Java, many home a chicken farmer, in thehamlet Parengan Kraton Sidoarjo district is very famous for animal breeding chicken. Productivity breeders requirewaste mustard chicken with the chopped in the hamlet Parengan Kraton Krian Sidoarjo can not meet the needs ofthe market, the acquisition of waste results from the traditional markets of 50-80 kg / day, were able to be processed5-15 kg / day using traditional tools ie by perajangan mustard waste manually. Some efforts to increase productionhave been made to spur the development of the farmer, from the conventional to modern process (machine).Therefore conducted research with the title : analysis of effect of round and distance (pitch) pisau to wasteproduction capacity in the machine chooper mustard mustard in the area. In this study the authors calculate thechopper machine design capacity mustard waste by means of varying the distance a knife (0.03 m; 0.04 m; 0.05 m)and the rotation axis (200Rpm, 300Rpm, 400rpm), while the fixed blade diameter, so that obtain optimal results andto determine the engine power is needed, with reference to 250 kg / h, and the conveniences expected chopperengine testing conducted to determine the waste mustard in actual production capacity, and compared with theproduction capacity of the calculation results. The achievement of a production capacity of 247.67 kg / hour is themost excellent results of chopped cabbage waste, using waste mesinperajang mustard dimensions: Diameter 0.28mknife, round knife 300Rpm with a distance of 0.04m. The results showed that the production capacity of wastemustard be 244.28 kg / h (Â± 250kg / h) using mustard waste chopper machine. Thus the research conducted by thepublic is expected to be implemented in order to further increase production and able to serve the market demand.Keywords : Waste chopper mustard, Distance knife, Round the machine.